Petrology and geochemistry of the S-type granite and the biotite-gneiss of the Etam granite-gneissic complex in the Pan African fold belt in Cameroon - Cyrille Sigue; Cheo Emmanuel Suh; Anicet Feudjio Tiabou; Pascal Landry Wabo Defo; Afahnwie Aloysius Ngambu; Jean Lavenir Ndema Mbongue; Guilianno Fossong (Discover Geoscience)
Abstract The Etam granite-gneissic complex is located in western part of the Tombel graben in the Central African Fold Belt in Cameroon. It includes plutonic rocks (coarse-grained granite, fine-grained granite and biotite granite) partially mylonitised and a metamorphic basement constituting gneiss and migmatites. Granites are syn- to post-tectonic and S-type, ferroan and strongly peraluminous. The high Rb/Sr (0.92–1.46) and low Sr/Ba (0.18–0.26) ratios coupled with an important negative Eu (Eu/Eu* = 0.37–0.59) anomaly characterize the lower degrees of crustal melting upon their formation accompanied with the dehydration of hydrous minerals as biotite. A CaO/Na2O ratio greater than 0.3 indicates that granites from Etam were derived from clay-poor, plagioclase-rich psammitic source material. Etam granites are peraluminous and display high potassic and alkali content. These characteristics are in line with the continental collision setting. The evidence of heterogeneous deformation in these rocks suggest syn to late collisional setting. The estimated crystallization temperature is resolved to be between 750 and 875 °C for Etam granites. Mylonites exhibit granitic composition with high SiO2 and Al2O3 contents similar to granites. Coarse-grained granite and mylonites show only little changes in magmatic minerals content. However, the grain size varies, decreasing from the coarse-grained granite to mylonite. The gneiss and mylonite plot in the igneous field in discrimination diagram. These characters suggest the igneous protoliths that are probably the surrounding coarse-grained granite for mylonite and an earlier intrusion for gneiss.